Comparing the Bacterial Community in the Gastrointestinal Tracts Between Growth-Retarded and Normal Yaks on the Qinghai–Tibetan Plateau - Ma, Jian; Zhu, Yixiao; Wang, Zhisheng; Yu, Xiong; Hu, Rui; Wang, Xueying; Cao, Guang; Zou, Huawei; Shah, Ali Mujtaba; Peng, Quanhui; Xue, Bai; Wang, Lizhi; et al. (Frontiers in Microbiology, 2020)
In ruminants, bacterial community in the gastrointestinal tract (GIT) have an essential role in the healthy growth. Examining the bacterial composition in the GIT between growth-retarded and normal yaks could improve our understanding about the role of microorganisms in yaks with growth retardation. In this study, 8 male yaks with growth retardation were used as the growth-retarded yak (GRY) group, and another 8 male growth normal yaks with same breed and age were used as the growth normal yak (GNY) group. We compared the bacterial community in the rumen, duodenum, jejunum, ileum, cecum, and colon between GRY and GNY groups based on the 16S rRNA gene sequencing. Alpha-diversity revealed that the Shannon index in the duodenum and ileum of GNY group was higher (P < 0.05) than that of GRY group. However, an opposite trend was found in the jejunum and cecum. The principal coordinates analysis showed that the bacterial structure in all segments of GIT differed from each other between 2 groups. In the rumen, the relative abundances of Ruminococcaceae NK4A214 group, Ruminococcaceae UCG-014, and Treponema 2 were higher (P < 0.05) in GNY group as compared to GRY group. However, the Christensenellaceae R-7 group exhibited an opposite trend. In the jejunum, compared to GNY group, the unclassified Chitinophagaceae was enriched significantly (P < 0.05) in GRY group. However, the unclassified Peptostreptococcaceae, Christensenellaceae R-7 group, and Lachnospiraceae NK3A20 group were enriched (P < 0.05) in GNY group. In the ileum, the relative abundances of Rikenellaceae RC9 gut group and Prevotellaceae UCG-004 were higher (P < 0.05) in GNY group than those in GRY group. In the cecum, the GNY group showed higher (P < 0.05) relative abundance of Prevotellaceae UCG-003 as compared to GRY group. In the colon, the relative abundances of Treponema 2 and unclassified Lachnospiraceae was slightly higher (0.05 < P < 0.10) in GNY group than those in GRY group. Overall, these results improve our knowledge about the bacterial composition in the GIT of growth-retarded and normal yaks, and regulating the bacterial community may be an effective solution to promote compensatory growth of growth-retarded yaks.